2021
DOI: 10.1126/science.abe1707
|View full text |Cite
|
Sign up to set email alerts
|

CARD8 is an inflammasome sensor for HIV-1 protease activity

Abstract: HIV-1 has high mutation rates and exists as mutant swarms within the host. Rapid evolution of HIV-1 allows the virus to outpace the host immune system, leading to viral persistence. Approaches to target immutable components are needed to clear HIV-1 infection. Here, we report that the CARD8 inflammasome senses HIV-1 protease activity. HIV-1 can evade CARD8 sensing because its protease remains inactive in infected cells prior to viral budding. Premature intracellular activation of the viral protease triggered C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
110
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(146 citation statements)
references
References 45 publications
(43 reference statements)
7
110
0
Order By: Relevance
“…1,3 ). This unique mechanism involving 'functional degradation' is conserved in the activation of human NLRP1 (hNLRP1) by the 3C proteases of enteroviruses 14 and in the activation of CARD8 by HIV-1 protease 15 .…”
mentioning
confidence: 99%
“…1,3 ). This unique mechanism involving 'functional degradation' is conserved in the activation of human NLRP1 (hNLRP1) by the 3C proteases of enteroviruses 14 and in the activation of CARD8 by HIV-1 protease 15 .…”
mentioning
confidence: 99%
“…First, for this mechanism to work, a cell has to express HIV Gag-Pol, and cells that express HIV proteins without ex vivo stimulation are exceedingly rare in ART-treated individuals [62]. Second, nevirapine, in comparison with other NNRTIs, has no such activity [58,59,61], but in our study, nevirapine was associated with the same levels of CA RNA as efavirenz and another study showed even lower levels of residual plasma viremia in nevirapine-treated compared to efavirenz-treated individuals [63]. This argues against induction of apoptosis of infected cells being a plausible mechanism behind the more pronounced virological suppression by NNRTIs.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy utilizes latency reversal agents (LRAs) to reactivate the latent reservoir (shock) and then induce targeted cell death of infected cells (kill) 7 . Optimal efficiency is needed for both steps of this strategy, but we recently reported that the inflammasome sensor caspase recruitment domain 8 (CARD8) is able to sense intracellular HIV-1 protease activity and induce targeted cell killing of HIV-1 infected cells 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated that one such PRR, CARD8, triggered the CASP1 activation and pyroptosis in human CD4 + T cells when cells were treated with the known Dipeptidyl Peptidase 9 (DPP9) inhibitor Val-boroPro (VbP) 11,12 . More recently, CARD8 was shown to sense intracellular HIV-1 protease activity 8 . CARD8 C-terminus (CARD8C) contains two key domains: the function-to-find domain (FIIND) and a CARD domain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation